2005
DOI: 10.2466/pms.101.1.43-54
|View full text |Cite
|
Sign up to set email alerts
|

The Sport Motivation Scale for Children: Preliminary Analysis in Physical Education Classes

Abstract: This study was done to test the psychometric properties of the modified version of the Sport Motivation Scale adapted for children in physical education. Participants were elementary school students (N = 452, M(age) = 13.9 +/- 1.04) who responded to the Sport Motivation Scale for Children. The scale assesses three types of motivation at the contextual level, namely, Intrinsic Motivation, Extrinsic Motivation, and Amotivation. Results supported the construct validity (CFI = .95), and internal consistency of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 19 publications
3
15
0
4
Order By: Relevance
“…The result also demonstrated that the sub dimension of fun is among the important reasons for female students. In the study of Zahariadis et al [35] where they measured the sport motivation of primary education students with the age average of 13, it was found that male students are more affected from the intrinsic motivation factors (physical fitness, skill development and competition)compared to the female students. Salguero et al [28] found in their study they conducted with 428 young Spanish swimmers that females give priority to fun and friendship sub dimensions rather than success and status, contrary to the males.…”
Section: Discussionmentioning
confidence: 99%
“…The result also demonstrated that the sub dimension of fun is among the important reasons for female students. In the study of Zahariadis et al [35] where they measured the sport motivation of primary education students with the age average of 13, it was found that male students are more affected from the intrinsic motivation factors (physical fitness, skill development and competition)compared to the female students. Salguero et al [28] found in their study they conducted with 428 young Spanish swimmers that females give priority to fun and friendship sub dimensions rather than success and status, contrary to the males.…”
Section: Discussionmentioning
confidence: 99%
“…Nenhum estudo verificando a estabilidade temporal da SMS-II foi encontrado na literatura até o momento, visto que esse instrumento foi recentemente publicado (PELLETIER et al, 2013). Estudos anteriores de validação da primeira versão da SMS para diferentes culturas encontraram valores semelhantes aos achados da presente pesquisa (BARA FILHO et al, 2011;NUÑEZ et al, 2006;PELLETIER et al, 1995;ZAHARIADIS;TSORBATZOUDIS;GROUIOS, 2005). Tais investigações apontam que os coeficientes inferiores a 0,70 podem estar relacionados principalmente às nuances conceituais e culturais entre a versão original e a traduzida, o que pode contribuir para diferentes compreensões da semântica do item.…”
Section: Discussionunclassified
“…Sin embargo, a pesar de ser una escala muy utilizada, en España no se encuentran trabajos en los que se comprueben las propiedades psicométricas del SMS adaptada a la EF, caso que si se da en otro países, como por ejemplo Grecia (Zahariadis et al, 2005). Por eso, se cree necesario aportar evidencias preliminares y exploratorias del SMS adaptada a la EF en una muestra de adolescentes españoles de educación secundaria.…”
unclassified